Diversity of National Legal Approaches for Protection of Geographical Indication in Africa: Rethinking the Best Option for Tanzania - Adrian Fulko Ndunguru; Romuald Haule; Elia Mwanga (Journal of International Trade, Logistics and Law, 2023)
The study was centered on the main objective of examining three approaches of protection of geographical indications which trademark system, sue generis system and the unfair competition system. This paper is intended to study various approaches of legal framework for protection of geographical indications as applied in different countries with the view of ascertaining the strength and weakness of each approach in order to recommended the right approach for Tanzania. The main problem which prompted the study is results from flexibility of the system for protection of geographical indications allowed by the WTO Agreement on Trade Related Aspects of Intellectual Property Rights of 1994. On part of methodology, the study is qualitative in nature and uses mainly secondary date derived by using documentary review of various international legal instruments, reports, legal text books, articles and conference papers based on protection of geographical indications. Data were analyzed by using content analysis in which the researcher sorted data basing on the relevancy of the content on the study objectives of the study. Generally, the findings has revealed that, apparently states protects geographical indications by using trademark laws, sue generis or specific laws and unfair competition system. However, the more comprehensive and effective approach that Tanzania can adopt is the sue generis system because it provided for specific standards for protection of geographical indications which cannot be mixed with trade mark or competition laws.